(untitled) (Journal of Forest and Livelihood, 2001)
Participatory action research plots were laid in 1997 in 3 purposively selected community forests in 3 middle hills districts in Nepal. These plots were subjected to various silvicultural treatments and monitored with active participation of FUGs. The findings revealed that the prescribed harvesting levels are far below the increment potential. This justifies more intensive use of forest, and this should be considered while preparing or revising operational plans.